Identification of major Babesia divergens polypeptides that induce protection against homologous challenge in gerbils. - Gorenflot, A (1990)
[35S]methionine-radiolabeled proteins from the Babesia divergens Rouen 1987 isolate were immunoprecipitated with immune sera from three potential hosts: human, ox, and gerbil. The results showed a constant humoral response against major babesial antigens. Similarly, immunoprecipitation of radiolabeled in vitro culture supernatant demonstrated that the exoantigens of 37, 46, 70, and 90 kDA were the immunodominant polypeptides, whatever the host. The effects of vaccination with concentrated supernatant from B. divergens Rouen 1987 in vitro cultures (30 to 40% parasitemia) were examined in gerbils inoculated with the homologous B. divergens isolate. Gerbils having received two or three injections of a whole vaccine dose (1.5 ml of parasitized culture supernatant equivalent [PCSE]) or of a 1:5 diluted vaccine dose (0.3 ml of PCSE) showed 100% survival after intraperitoneal challenge with 10(6) B. divergens-infected gerbil erythrocytes. Moreover, two or three injections of a 1:25 diluted vaccine dose (0.06 ml of PCSE) or 9% NaCl or 1.5 ml of unparasitized culture supernatant equivalent resulted in a mortality rate of 80 to 90% of the infected gerbils. Immunoprecipitation and immunofluorescence assays performed with antisera from vaccinated and control gerbils demonstrated that a single vaccine injection induced a humoral response, which increased slightly after the second or third injection. After challenge, antibody levels increased significantly, although the immunoprecipitation did not display any modification of Babesia antigen patterns.